2017
DOI: 10.1111/cdep.12269
|View full text |Cite
|
Sign up to set email alerts
|

Common Ground and Development

Abstract: Language and other forms of communication are inherently ambiguous and therefore require some form of common ground to specify the intended meanings of utterances. Theoretical accounts usually focus on interactions between adults and consider recursive mindreading a prerequisite to establishing common ground. Contrasting these accounts, in this article, we offer a developmental perspective on common ground. We propose that instead of using recursive mindreading, infants rely initially on the expectation that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

5
5

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 40 publications
0
49
0
Order By: Relevance
“…Thus, semantic ambiguity can be resolved by reasoning about why the speaker produced this particular utterance (H. H. Clark, 1996;Grice, 1991;Sperber & Wilson, 2001;Tomasello, 2008). On the other hand, there is information provided by common ground (the body of knowledge and beliefs shared between interlocutors) (Bohn & Koymen, 2018; E. V. Clark, 2015;H. H. Clark, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, semantic ambiguity can be resolved by reasoning about why the speaker produced this particular utterance (H. H. Clark, 1996;Grice, 1991;Sperber & Wilson, 2001;Tomasello, 2008). On the other hand, there is information provided by common ground (the body of knowledge and beliefs shared between interlocutors) (Bohn & Koymen, 2018; E. V. Clark, 2015;H. H. Clark, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this, developmental research has shown that the interaction between commonsense psychology and language understanding is at work from early in life. By age two, children are already sensitive to other people's knowledge (Bohn, Zimmerman, Call, & Tomasello, 2018;Southgate, Chevallier, & Csibra, 2010;O'Neill, 1996), past experience (Saylor, Ganea, & Vazquez, 2011;Saylor & Ganea, 2007), visual perspective (Vaish, Demir, & Baldwin, 2011;Koenig & Echols, 2003;Baldwin, 1991), and information in common ground (Liebal, Carpenter, & Tomasello, 2010;Akhtar, Carpenter, & Tomasello, 1996;Moll & Tomasello, 2006; see Bohn & Köymen, 2018 for review); although these capacities continue to develop throughout early childhood (Moll, Carpenter, & Tomasello, 2011;Nilsen & Graham, 2009;Morisseau, Davies, & Matthews, 2013). These studies show that the building blocks RUNNING HEAD: SOCIAL PRAGMATICS 4 necessary for reference resolution are in place in early childhood.…”
Section: Running Head: Social Pragmaticsmentioning
confidence: 99%
“…The second psychological construct in our framework is common ground. Common ground refers to bits of information that are assumed to be shared between interlocutors and constitutes the background against which utterances are interpreted (Bohn & Köymen, 2018, H. H. Clark, 1996, E.V. Clark, 2009.…”
Section: Observable Variablesmentioning
confidence: 99%